A Qualitative Study of Pokémon Go Players' Behaviors, Motivation, & Perception - Oh, Yoonsin; Rodriguez, Sebastian Antonsen; Bugel, Allison; Castaneda, Illyanna; Clark, Gracia; Brunett, Allie (My University, 2018)
The brand Pokémon has been popular among youth since it came out in the early 1990s (Tobin, 2004). Pokémon Go was released on July 6th, 2016. This study investigated Pokémon Go players to determine why some people stopped playing the game and why some people still continue to play. In this study, we focused on people's play behavior, motivation, and health perceptions.
Color poster with text and table.
Keywords: Posters; Pokémon Go; Exergames; Alternative reality games; Fitness walking